The fabrication and testing drifting buoys of marine data collection - Le, Van Cong; Phan, Hong Minh; Nguyen, Kieu Hung (Vietnam Journal of Marine Science and Technology, 2024)
This paper presents the primary contents of successfully researching, designing and manufacturing drifting buoys to collect marine data to measure temperature, salinity, and ocean currents in surface layers. The paper presents the basic information about the structure, specifications, the buoys working as the laboratory results, and field tests of drift buoys at sea. The drifting buoy test results at the sea of Van Don - Quang Ninh area met the criteria of water-tightness, buoyancy, and balance; the ability to collect temperature and salinity data of the sensors; the ability to transmit and receive information from drifting buoy at sea to the central computer via a web server; operability of the parachute and the travel of the buoy. The buoy database management software is on the website at http://vnsea.vn. It manages the collected data in real-time, showing the parameters and their variables in space and time, the buoy’s tracking on the Google map.